Genome-wide specificity of highly efficient TALENs and CRISPR/Cas9 for T cell receptor modification - Knipping, Friederike; Petri, Karl; Glimm, Hanno; Kalle, Christof von; Schmidt, Manfred; Gabriel, Richard (Molecular therapy. Methods & clinical development, 2017)
In T cells with transgenic high-avidity T cell receptors (TCRs), endogenous and transferred TCR chains compete for surface expression and may pair inappropriately, potentially causing autoimmunity. To knock out endogenous TCR expression, we assembled 12 transcription activator-like effector nucleases (TALENs) and five guide RNAs (gRNAs) from the clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated (Cas9) system. Using TALEN mRNA, TCR knockout was successful in up to 81% of T cells. Additionally, we were able to verify targeted gene addition of a GFP gene by homology-directed repair at the TALEN target site, using a donor suitable for replacement of the reporter transgene with therapeutic TCR chains. Remarkably, analysis of TALEN and CRISPR/Cas9 specificity using integrase-defective lentiviral vector capture revealed only one off-target site for one of the gRNAs and three off-target sites for both of the TALENs, indicating a high level of specificity. Collectively, our work shows highly efficient and specific nucleases for T cell engineering.